The Influence of Consumer Behavior and Product Quality on Consumer Decision Making in Choosing Funds as a Financial Technology Mobile Payment Application - Budi Rustandi Kartawinata; Agung Raya (Universitas Muhammadiyah Prof. DR HAMKA., 2021)
As technology advances and becomes more sophisticated, consumer behavior patternss shift. The presence of such events stimulates diverse corporate industries to compete in order to develop innovation. Businesses in the field of financial technology also use it (Fintech). DANA is a mobile payment application that supports ATM cards for online purchases. Despite the fact that DANA is a new program, it is capable of adapting fast in order to attract users. DANA has proven to be the third most popular app in Indonesia, with the most users and the most downloads. The goal of this research is to analyse the influence of customer behavior and product quality on the selection to use DANA as a mobile payment application. This type of research is quantitative by using descriptive data analysis techniques that use multiple linear hypothesis models with a total of 400 research samples. The results obtained from this study that consumer behavior and quality productx have a significant and positive effect on partial (individual) decision making.As for the results of simultaneous testing (collectively) on consumer behavior and product quality to consumer decision making in choosing DANA as a mobile payment application has a significant effect and the results are accepted.